Analgesic opioid use disorders in patients with chronic non-cancer pain: A holistic approach for tailored management. (February 2021) - Bertin, Célian; Delage, Noémie; Rolland, Benjamin; Pennel, Lucie; Fatseas, Mélina; Trouvin, Anne-Priscille; Delorme, Jessica; Chenaf, Chouki; Authier, Nicolas
Highlights: Chronic pain management could be complicated by substance use disorder history. A holistic management could manage both the main pathology and associated comorbidities. This holistic approach requires a coordinated, multidisciplinary, and language-shared care network. This individualized care improves the patient's overall quality of life by limiting drug inflation. Abstract: Chronic pain is a major public health issue that frequently leads to analgesic opioid prescriptions. These prescriptions could cause addiction issues in high-risk patients with associated comorbidities, especially those of a psychiatric, addictive, and social nature. Pain management in dependent patients is complex and is yet to be established. By combining the views of professionals from various specialties, we conducted an integrative review on this scope. This methodology synthesizes knowledge and results of significant practical studies to provide a narrative overview of the literature. The main results consisted in first proposing definitions that could allow shared vocabulary among health professionals regardless of their specialties. Next, a discussion was conducted around the main strategies for managing prescription opioid dependence, as well as pain in the context of opioid dependence and associated comorbidities. As a conclusion, we proposed to define the contours of holistic management by outlining the main guidelines for creating a multidisciplinary care framework for multi-comorbid patients with chronic pathologies.